A study of the distributions underlying business survey responses in New Zealand - Cassino, Vincenzo (School of Management Working Papers, 1994)
This study examines the distributions underlying business survey responses in New Zealand. These distributions are used in procedures which derive quantitative statistics from qualitative survey data. They are also used in an econometric procedure recently developed by the French economist Marc Ivaldi which uses survey data to test structural economic models. These procedures often assume that the distributions are normal. The purpose of this study is to examine the empirical validity of this assumption. The polychoric correlation coefficient procedure is used to test the goodness of fit of a standardised bivariate normal distribution on data from the New Zealand Institute of Economic Research’s Quarterly Survey of Business Opinion.